(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Traditional, teacher-centered classrooms have long dominated the educational landscape. However, a growing body of research highlights the transformative potential of cooperative pedagogy. This approach emphasizes collaboration, interaction, and shared responsibility for learning among students. By harnessing the power of teamwork, cooperative learning unlocks a range of possibilities for increased learning effectiveness.